Impact of gut microbial diversity on egg production performance in chickens - Liping Wu; Tao Zhang; Zhihua Luo; Huiyuan Xiao; Di Wang; Cailong Wu; Xinyan Fang; Jiawei Li; Jing Zhou; Junjie Miao; Hongli Tan; Yanan Wang; et al. (Microbiology Spectrum)
ABSTRACT Chickens are one of the most economically important poultry species, and their egg-laying performance is a crucial economic trait. The intestinal microbiome plays a significant role in the egg-laying performance. To clarify the diversity of chicken intestinal microbiota and its connection to egg-laying performance, this study utilized 16S rRNA sequencing technology to characterize the intestinal microbiomes of 101 chickens from 13 breeds with varying levels of egg production. The results reveal significant differences in gut microbiota structure among chicken groups with varying egg production levels. High egg-producing chickens showed significantly higher abundances of Firmicutes, Proteobacteria, and Lactobacillus, while low egg-producing chickens displayed greater microbial α-diversity and more complex community structures. These differences in gut microbiota influence key physiological functions, including nutrient absorption and hormone regulation through metabolic pathways, and directly affect egg production performance. The low and medium production groups partially overlapped on the principal coordinates analysis plot, whereas the high-production group was distinctly separate. This study provides a scientific basis and intestinal microbiome data for selecting probiotics related to high egg production in chickens.IMPORTANCEThis study elucidates the critical role of gut microbiota in the egg-laying performance of chickens, a key economic indicator in the poultry industry. By employing 16S rRNA sequencing, we uncovered distinct microbial profiles associated with varying levels of egg production. High egg-producing chickens exhibit a higher abundance of specific bacterial taxa, such as Firmicutes and Proteobacteria, which are linked to enhanced nutrient absorption and metabolic efficiency. Conversely, lower and medium egg-producing chickens display greater microbial diversity, suggesting a more complex but less efficient gut ecosystem. Our findings provide valuable insights into the relationship between gut microbiota and egg production, offering a scientific foundation for the selection of probiotics that could potentially improve the egg-laying performance of chickens. This research not only advances our understanding of avian gut microbiology but also has practical implications for optimizing poultry farming practices and enhancing economic outcomes.